2002
DOI: 10.1104/pp.005314
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Cultivated Tomato to Cell Content-Feeding Herbivores Is Regulated by the Octadecanoid-Signaling Pathway

Abstract: The octadecanoid signaling pathway has been shown to play an important role in plant defense against various chewing insects and some pathogenic fungi. Here, we examined the interaction of a cell-content feeding arachnid herbivore, the two-spotted spider mite (Tetranychus urticae Koch), with cultivated tomato (Lycopersicon esculentum) and an isogenic mutant line (defenseless-1 [def-1]) that is deficient in the biosynthesis of the octadecanoid pathway-derived signal, jasmonic acid (JA). Spider mite feeding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
227
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(253 citation statements)
references
References 50 publications
21
227
2
3
Order By: Relevance
“…Third, the reduced density of type-VI trichomes on jai1 leaves was correlated with a profound loss of resistance to two-spotted spider mites. This observation is in agreement with studies showing that type-VI trichomes mediate the effective resistance of wild tomato species to spider mites and that the defense of cultivated tomato to this herbivore is regulated by endogenous JAs derived from the octadecanoid pathway (Kennedy, 2002;Li et al, 2002a). Finally, a role for LeCOI1 in glandular trichome function is supported by the effect of jai1 on defense-related exudate chemistry, including the reduced accumulation of monoterpenes that exert defensive action against insect pests (Mahmoud and Croteau, 2002;Pichersky and Gershenzon, 2002).…”
Section: Role Of Coi1 In Glandular Trichome Development and Anti-herbsupporting
confidence: 81%
“…Third, the reduced density of type-VI trichomes on jai1 leaves was correlated with a profound loss of resistance to two-spotted spider mites. This observation is in agreement with studies showing that type-VI trichomes mediate the effective resistance of wild tomato species to spider mites and that the defense of cultivated tomato to this herbivore is regulated by endogenous JAs derived from the octadecanoid pathway (Kennedy, 2002;Li et al, 2002a). Finally, a role for LeCOI1 in glandular trichome function is supported by the effect of jai1 on defense-related exudate chemistry, including the reduced accumulation of monoterpenes that exert defensive action against insect pests (Mahmoud and Croteau, 2002;Pichersky and Gershenzon, 2002).…”
Section: Role Of Coi1 In Glandular Trichome Development and Anti-herbsupporting
confidence: 81%
“…This suggests that T. urticae induces plant defences that hamper the reproductive performance of other spider mites, not only through JA signalling. Previous studies showed higher reproductive performance of spider mites on a def-1 tomato mutant compared with a wild tomato (Li et al, 2002;Ament et al, 2004), but recent studies show circumstantial evidence for antiherbivore defences mediated by salicylic acid, another signal transducer mediating the expression of plant defence genes (Farouk and Osman, 2011, but see Kawazu et al, 2011). Although we recognize the possibility of a role for plant defences that are not mediated by JA, we emphasize that this does not change our conclusion regarding the impact of RI.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel experiment, we created a strong RI treatment in the founder generation by releasing heterospecific and conspecific males with virgin females, which can then mate with conspecific and heterospecific males, the latter of which can potentially result in decreased reproduction. A second advantage of using the two species of spider mites is that there is much knowledge of the impact they have on host plant defences: within leaves of tomato plants many strains of T. urticae induce the jasmonate(JA)-mediated plant defences (Li et al, 2002;Ament et al, 2004;Kant et al, 2004Kant et al, , 2008, whereas T. evansi downregulates these defences, even below household levels (Sarmento et al, 2011a), thereby making the host plant more profitable for both T. evansi and T. urticae (Sarmento et al, 2011b). By using mutant def-1 tomato plants that are deficient in mounting JA-mediated plant defences (Howe et al, 1996;Li et al, 2002;Ament et al, 2004;Kant et al, 2008), we were able to reduce the effect of JA-mediated plant defences in our competition experiments, thereby gaining more analytic power to detect RI.…”
Section: Introductionmentioning
confidence: 99%
“…Our reduction-of-function study demonstrates that LeMPK1 and LeMPK2 are required for systemin-mediated resistance to M. sexta larvae. Antisense expression of prosystemin in transgenic tomato plants resulted in reduced defense protein accumulation and thus loss of resistance to M. sexta (6), whereas 35S::prosys plants exhibited high constitutive levels of defense proteins and increased resistance to M. sexta (1) and other insects (46). MPK1 and MPK2 play an essential role for systemin-induced defense protein synthesis, and the presence of MPK3 cannot compensate for the loss of MPK1 and MPK2 (Fig.…”
Section: Discussionmentioning
confidence: 99%